Perancangan Sistem Kendali Quadcopter Menggunakan Modified Sliding Mode Control - Rudi Uswarman; Swadexi Istiqphara (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Quadcopter has nonlinear dynamics that require a robust controller to be able to fly stably. This paper uses a nonlinear controller, namely Sliding Mode Control (SMC). SMC has advantages such as robust from disturbance and uncertainty of parameters and ability to maintain stability, even when the dynamics model is not precise. The simulation compares the reliability of conventional SMC and modified SMC controls. Modified SMC control has the purpose of increasing the robustness of control system from disturbance and uncertainty. Based on the simulation, the modified SMC control has better reliability than conventional SMC. In conventional SMC control, the quadcopter response on the x-axis, to the reference position, has overshoots of 0.7 meters and 0.48 meters; and an undershoot of 0.45 meters. Then, the y-axis movement response has an overshoot of 0.3 meters and undershoots of 0.3 meters and 0.48 meters. The conventional SMC output of the z-axis movement has an undershoot of 1.75 meters, while on the modified SMC control, there are only overshoot and undershoot of 0.3 meters on the y-axis movement. Modified SMC control is more reliable than conventional SMC controls because the switching control of the modified SMC can adaptively change, according to the error caused by interference. The greater the uncertainty, the greater the error. A large error can increase the switching control frequency, so that the level of robustness will increase